2015
DOI: 10.1177/1934578x1501000118
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Biological Evaluation of Selected African Propolis Samples from Cameroon and Congo

Abstract: The objective of this study was the chemical analysis of four selected samples of African propolis (Congo and Cameroon) and their biological evaluation. Twenty-one secondary metabolites belonging to four different chemical groups were isolated from the 70% ethanolic extracts of propolis and their structures were elucidated on the basis of spectral evidence. Three triterpenes and two diprenyl-flavonoids were identified from Congo propolis, which has been investigated for the first time, while thirteen triterpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…In subtropical eastern Australia, pentacyclic triterpenoids and C ‐prenylated flavonoids, including abyssinoflavanone VII, propolin C and nymphaeol C, were identified (Massaro et al ., ). In Africa, three triterpenes and two diprenyl‐flavonoids were identified in Congo propolis, while thirteen triterpenes, three diprenyl‐flavonoids, two monoterpenic alcohols and one fatty acid ester have been identified in Cameroon propolis samples (Papachroni et al ., ).…”
Section: Propolis Chemical Composition and The Problem Of Standardizamentioning
confidence: 97%
“…In subtropical eastern Australia, pentacyclic triterpenoids and C ‐prenylated flavonoids, including abyssinoflavanone VII, propolin C and nymphaeol C, were identified (Massaro et al ., ). In Africa, three triterpenes and two diprenyl‐flavonoids were identified in Congo propolis, while thirteen triterpenes, three diprenyl‐flavonoids, two monoterpenic alcohols and one fatty acid ester have been identified in Cameroon propolis samples (Papachroni et al ., ).…”
Section: Propolis Chemical Composition and The Problem Of Standardizamentioning
confidence: 97%
“…Previous studies conducted in sub-Saharan Africa have revealed propolis from this region to contain a high terpenoid content. 26,30 This has been confirmed by researchers, such as Zhang et al, 30 who investigated propolis samples from Uganda, Tanzania, Malawi, Zambia, South Africa, Cameroon, Nigeria, and The Gambia. They concluded that African propolis was rich in diterpenoids and triterpenoids.…”
Section: Resultsmentioning
confidence: 62%
“…Papakroni et al 26 found, for the first time, triterpenes, such as lupennon, β-amirin and lupeol, diprenyl-flavonoid lonchocarpol, and 6,8-diprenyl-eriodictyol in propolis samples from the Democratic Republic of Congo. Rushdi et al 27 found α-amyrin, β-amyrin, α-amyryl acetates, β-amyryl acetates, n-alkanes, n-alkenes, methyl n-alkanoates, and long-chain wax esters in propolis samples from Ethiopia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as contribution to the chemical profiling of selected samples of African propolis using dereplication (LC-HRMS), a sample of propolis from Cameroon was proven to be significantly rich in triterpenoids [21]. Another detailed study revealed three diprenyl-flavonoids, thirteen triterpenes, one fatty acid ester and two monoterpenic alcohols in Cameroonian propolis samples from Oku (North-west Region), Ngaoundal and Tekel (Adamawa region) [22].…”
Section: Cameroonmentioning
confidence: 99%